Go Formative for Formative Assessment Feedback on the 10th Graders’ Material Comprehension and Learning Motivation - Pangarso, Zulkaisi Dwi; Istiyono, Edi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Feedback on formative assessment is a teacher's effort to help students with learning difficulties by responding to their evaluation results, especially on HOTS-based evaluations, which have a higher level of completion. Therefore, this study aims to determine the effect of immediate feedback on improving Material Comprehension (MC) and Learning Motivation (LM). Unfortunately, the teacher needs to provide feedback due to several factors, one of which is time constraints due to teachers’ activity. This study aims to investigate the effect of Go Formative in providing immediate feedback on formative physics assessments on material comprehension and learning motivation enhancement of 10th-grade high school students. This research is quasi-experimental with a non-equivalent control group design involving two classes, namely the control and experimental classes. The two classes were selected by employing a simple random sampling technique. This study's results show a different effect of using Go Formative in providing quick feedback in improving students' material comprehension. The existence of these differences makes the provision of quick and immediate feedback through the Go Formative website a solution to overcome the obstacles experienced by teachers in carrying out formative assessments.